Ultrafast hydrothermal assembly of nanocarbon microfibers in near-critical water for 3D microsupercapacitors - Zhai, Shengli (2020)
Translating the advantages of carbon nanomaterials into macroscopic energy storage devices is challenging because the desirable nanoscale properties often disappear during assembly processes. Here we describe a new nonequilibrium subcritical hydrothermal method capable of independently manipulating the temperature and pressure to create unique assembly conditions crossing the commonly used liquid-vapor boundary. Highly conductive and dense-packed yet ion-accessible nanocarbon microfibers can be obtained from graphene oxide sheets, single-walled carbon nanotubes, and a nitrogen-doping crosslinker under 20 min of hydrothermal assembly, 80% energy saving compared to standard hydrothermal methods, and one of the shortest time in the field of hydrothermal processing of carbon nanomaterials. Using those microfibers, we built microsupercapacitors that reach a high volumetric capacitance of 52 F cm−3, energy density of 7.1 mWh cm−3, and power density of 1645.7 mW cm−3, respectively. We further demonstrate the 3D integration of multiple fiber microsupercapacitors that reduces the device footprint by 75% while expanding the operational voltage and current window. This strategy is a promising tool for harmoniously assembling carbon nanostructures as energy storage components for various energy applications.